PERAN GURU DALAM MENINGKATKAN PERILAKU ISLAMI SISWA SMA N 2 OKU - Dewa Ikhram; Muhammad Win Afgani; Fajri Ismail (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2023)
Education is so very important to change human morals, especially the many moral declines committed by children and adolescents. In this case, it is a tough task for the three education centers, both in the family, school and community. These three educational institutions should work together to achieve Islamic educational goals.